2000
DOI: 10.1107/s0108768100000501
|View full text |Cite
|
Sign up to set email alerts
|

On the inclusion of solvent molecules in the crystal structures of organic compounds

Abstract: The Cambridge Structural Database has been searched for all crystal structures including organic solvent molecules (solvates) and solvent water molecules (hydrates). Well above 300 different solvent molecules were identified and the frequencies with which they occur in crystal structures, as a function of the year of publication, were established. The crystal structures are classified as 'organic' and 'metalloorganic'; it is shown that the relative prevalences of various cocrystallized solvents are different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 4 publications
0
102
0
Order By: Relevance
“…For transition metals, this interaction is particularly strong. In fact, 5.7% of the metal-organic structures listed in the CSD [15] in 2000 include water as ligand to the metal ion, more than any other solvent molecule [51]. These aquo complexes reveal significant stability with water loss occurring well above the boiling point of liquid water, probably as a result of ion dipole interactions with the metal centre.…”
Section: Single Crystal X-ray Structures Of Hydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…For transition metals, this interaction is particularly strong. In fact, 5.7% of the metal-organic structures listed in the CSD [15] in 2000 include water as ligand to the metal ion, more than any other solvent molecule [51]. These aquo complexes reveal significant stability with water loss occurring well above the boiling point of liquid water, probably as a result of ion dipole interactions with the metal centre.…”
Section: Single Crystal X-ray Structures Of Hydratesmentioning
confidence: 99%
“…Desiraju [16] has investigated a test-set of 411 hydrate crystal structures and found that although manifold factors play a role in hydrate formation, this process is more likely to happen when the host molecule shows an imbalance between the number of hydrogen bond donor and acceptor groups. Gorbitz and Hersleth [17] have discussed the increase in recent years of occurrence of solvated crystal forms, including hydrates and mixed solvates (i.e., water and an organic solvent), and conclude that this increase is due to the increasing complexity of modern molecules and their reduced packing efficiency. Infantes and Motherwell [18] investigated 1516 organic hydrate structures of the CSD with a view to classifying water clusters.…”
Section: Single Crystal X-ray Structures Of Hydratesmentioning
confidence: 99%
“…Although over 300 solvents are represented in the CSD, 28 only five solvents will be discussed in this article. Two alcohols, ethanol and methanol, and two apolar chlorinated solvents, dichloromethane and chloroform were selected.…”
Section: Introductionmentioning
confidence: 99%
“…However, solvent molecules in the crystal lattice can also create strong interactions and hydrogen bonding with APIs and other solvent molecules to form flexible clusters, which can improve the stability of metastable solid forms [39][40][41][42][43]. Solvent molecules may also play a role of space fillers in the crystal lattice without forming strong interactions with host molecules [44,45].…”
Section: Principles Of Water and Solvent Associationsmentioning
confidence: 99%